Separateness or wholeness: a qualitative study of the experiences of Asian American female sexual minorities - Zhang, Bin; Park, Gilbert; Chang, Bo; Du, Wenqian (Frontiers in Psychology, 2024)
This study explored the intersection of race, gender, and sexuality as they pertain to experiences of Asian American female sexual minority (AAFSM) students attending Midwestern universities in the United States through an intersectional lens. The study utilized intersectionality as a theoretical framework, a data generation tool, and a methodological approach to guide the study. The results showed that the participants experienced constructed objectifications, which included gendered, racial, and sexual objectification. The findings also revealed that participants’ race, gender, and sexual orientation were contextualized based on the situation. Further, participants devalued their Asianness, womanhood, and LGBTQness owing to the lack of positive representation in the curriculum. The analyzed data can be best categorized as the lack of intersectional representations in curricula, contextualized race, gender, and sexuality, and reported experiences of constructed objectifications. Discussions provided an inclusive campus environment for participants who were AAFSMs. These discussions also provided meaningful suggestions for educators, administrators, policymakers, and stakeholders to foster an equal and equitable educational environment for students with multiple marginalized identities.